Composite pole piece and battery
By designing composite electrode sheets in the battery, using the combination of conductive polymer and active material layers to form dynamic hydrogen bonds to enhance connections, the problem of the risk of fire at high temperatures is solved, and the safety and electrical performance of the battery are achieved Improvement.
Patent Information
- Application Number
- CN202411354655.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
Semi-solid state batteries still have a fire risk in high temperature environments, and a composite electrode and its battery are needed to effectively reduce the risk of fire.
A composite electrode sheet is designed, including a current collector layer, a conductive polymer layer and an active material layer. The conductive polymer layer is composed of a conductive polymer, polyethylene oxide and an oxide solid electrolyte. The active material layer is composed of a positive electrode active material. , binder, conductive agent and polyacrylonitrile. The conductive polymer layer is located between the positive electrode current collector and the active material layer. Polyacrylonitrile enhances the connection between the conductive polymer and the active material layer through dynamic hydrogen bonding, reducing the interface resistance and Improve battery safety.
It effectively prevents the occurrence of thermal runaway, improves the safety and electrical performance of the battery, and reduces the risk of the battery's fire.
Smart Images

Figure CN119208938A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a composite pole piece and a battery. Background Art
[0002] Secondary batteries conventionally use liquid electrolytes, which contain a large amount of flammable and leaky organic carbonate small molecule solvents, posing a major safety hazard. The electrolyte of semi-solid batteries adopts a solid-liquid mixed form, combining the safety of solid-state batteries with the cost advantages of traditional liquid batteries.
[0003] Although the safety of semi-solid-state batteries is improved, there is still a risk of fire in high temperature environments. Summary of the invention
[0004] Based on this, it is necessary to provide a composite electrode and a battery thereof that reduce the risk of fire.
[0005] In a first aspect, the present application provides a composite pole piece, comprising a current collector layer, wherein at least one side of the current collector layer has a conductive polymer layer and an active material layer formed in sequence along a direction away from the current collector layer; the conductive polymer layer comprises a conductive polymer, polyethylene oxide and an oxide solid electrolyte, and the active material layer comprises a positive electrode active material, a binder, a conductive agent and polyacrylonitrile.
[0006] In the above-mentioned composite pole piece, a conductive polymer layer and an active material layer are sequentially formed on the current collector layer. The conductive polymer layer includes a conductive polymer, polyethylene oxide and an oxide solid electrolyte, and the active material layer includes a positive electrode active material, a binder, a conductive agent and polyacrylonitrile. In the conductive polymer layer, the conductive polymer provides an electron transmission channel, the polyethylene oxide provides an ion transmission channel, and the conductive polymer layer is located between the positive electrode current collector and the positive electrode active material layer. In the early stage of thermal runaway of the battery, the conductive polymer and the ion-conducting polymer (polyethylene oxide) chain segments are broken due to excessive temperature, and the conductive path of the positive electrode active material and the current collector layer is disconnected, thereby preventing the occurrence of thermal runaway. In the active material layer, polyacrylonitrile is contained as a polymer electrolyte to improve ionic conductivity, and has high temperature resistance and flame retardant effects, further preventing the occurrence of thermal runaway. In addition, the conductive polymer polyacrylonitrile in the active material layer is a polymer phase, and a large number of dynamic hydrogen bonds (CN-HO) are formed between the cyano group in the polymer phase polyacrylonitrile and the hydroxyl group at the end of the polyethylene oxide chain. This supramolecular interaction weakens the phase separation, thereby strengthening the direct connection between the conductive polymer and the active material layer, reducing the interface resistance, and effectively improving the battery electrical performance while improving the battery safety.
[0007] In one embodiment, the conductive polymer includes one or more combinations of polyaniline, polypyrrole, and polythiophene.
[0008] In one of the embodiments, the thickness ratio of the conductive polymer layer to the active material layer is (2-5): (70-90).
[0009] In one of the embodiments, in the conductive polymer layer, the mass percentage of the conductive polymer is 30% to 50%; the mass percentage of polyethylene oxide is 5% to 20%.
[0010] In one embodiment, in the conductive polymer layer, the mass percentage of polyethylene oxide is 8% to 15%.
[0011] In one of the embodiments, the mass percentage of polyacrylonitrile in the active material layer is 1% to 8%.
[0012] In one of the embodiments, the mass percentage of polyacrylonitrile in the active material layer is 1% to 4%.
[0013] In one embodiment, the active material layer further comprises sericin.
[0014] In one embodiment, the mass percentage of the sericin in the active material layer is 1%-2%.
[0015] In a second aspect, the present application further provides a battery, comprising the composite electrode sheet, a negative electrode sheet and an electrolyte, wherein the electrolyte comprises a tetraethylene glycol dimethyl ether solvent.
[0016] In the above battery, by adding tetraethylene glycol dimethyl ether to the electrolyte, polyethylene oxide and tetraethylene glycol dimethyl ether can be cross-linked to form a cross-linked phase, thereby reducing the crystallinity of polyethylene oxide, making the polyethylene oxide chain segments more flexible in the electrochemical process. On the one hand, the ionic conductivity of polyethylene oxide can be improved, and on the other hand, more hydroxyl groups at the ends of the polyethylene oxide chains can form dynamic hydrogen bonds (CN-HO) with the cyano groups in polyacrylonitrile.
[0017] In one embodiment, the mass percentage of tetraethylene glycol dimethyl ether in the electrolyte is 4% to 10%.
[0018] In one embodiment, the electrolyte includes bis(trifluoromethanesulfonyl)imide lithium salt, which accounts for 1% to 5% by mass of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] FIG. 1 is a schematic structural diagram of a composite pole piece according to an embodiment.
[0020] FIG. 2 is a schematic diagram of a method for preparing a composite electrode according to an embodiment. DETAILED DESCRIPTION
[0021] References to embodiments of the present application will now be provided in detail, one or more examples of which are described below. Each example is provided as an explanation rather than a limitation of the present application. In fact, it will be apparent to those skilled in the art that various modifications and variations may be made to the present application without departing from the scope or spirit of the present application. For example, a feature described or described as part of one embodiment may be used in another embodiment to produce a further embodiment.
[0022] Therefore, it is intended that the present application covers such modifications and variations that fall within the scope of the appended claims and their equivalents. Other objects, features and aspects of the present application are disclosed in or are apparent from the following detailed description. It will be appreciated by those of ordinary skill in the art that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the present application.
[0023] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.
[0024] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.
[0025] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0026] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0027] If there is no special explanation, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S12 and S14, which means that the method may include steps S12 and S14 performed sequentially, or may include steps S14 and S12 performed sequentially. For example, it is mentioned that the method may also include step S16, which means that step S16 may be added to the method in any order. For example, the method may include steps S12, S14 and S16, or may include steps S12, S16 and S14, or may include steps S16, S12 and S14, etc.
[0028] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0029] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0030] A composite pole piece includes a current collector layer, at least one side of the current collector layer is sequentially formed with a conductive polymer layer and an active material layer in a direction away from the current collector layer, the conductive polymer layer includes a conductive polymer, polyacrylonitrile and an oxide solid electrolyte, and the active material layer includes a positive electrode active material, a binder, a conductive agent and polyethylene oxide.
[0031] For example, referring to FIG. 1 , FIG. 1 shows a schematic diagram of the structure of a composite electrode in an embodiment, a conductive polymer layer 11 is formed on a current collector layer 10, and an active material layer 12 is formed on the conductive polymer layer 11. In some embodiments, a conductive polymer layer 11 is formed on both sides of the current collector layer 10, and an active material layer 12 is formed on both sides. It should be noted that the thickness relationship between the current collector layer 10, the conductive polymer layer 11, and the active material layer 12 in FIG. 1 is only for illustration and does not constitute a limitation on the scope of protection of the present application.
[0032] Illustratively, the current collector layer may be an aluminum foil, a copper foil, or a composite current collector.
[0033] In the above-mentioned composite pole piece, a conductive polymer layer and an active material layer are sequentially formed on the current collector layer. The conductive polymer layer includes a conductive polymer, polyethylene oxide and an oxide solid electrolyte, and the active material layer includes a positive electrode active material, a binder, a conductive agent and polyacrylonitrile. In the conductive polymer layer, the conductive polymer provides an electron transmission channel, the polyethylene oxide provides an ion transmission channel, and the conductive polymer layer is located between the positive electrode current collector and the positive electrode active material layer. In the early stage of thermal runaway of the battery, the conductive polymer and the ion-conducting polymer (polyethylene oxide) chain segments are broken due to excessive temperature, and the conductive path of the positive electrode active material and the current collector layer is disconnected, thereby preventing the occurrence of thermal runaway; the active material layer contains polyacrylonitrile as a polymer electrolyte to improve ionic conductivity, and has high temperature resistance and flame retardant effects, further preventing the occurrence of thermal runaway. In addition, the conductive polymer polyacrylonitrile in the active material layer is a polymer phase, and a large number of dynamic hydrogen bonds (CN-HO) are formed between the cyano group in the polymer phase polyacrylonitrile and the hydroxyl group at the end of the polyethylene oxide chain. This supramolecular interaction weakens the phase separation and strengthens the connection between the polymer phase and the cross-linked phase, thereby strengthening the direct connection between the conductive polymer and the active material layer, reducing the interface resistance, and effectively improving the battery electrical performance while improving the battery safety.
[0034] In some embodiments, the conductive polymer includes one or more combinations of polyaniline, polypyrrole, and polythiophene.
[0035] In some embodiments, the thickness ratio of the conductive polymer layer to the active material layer is (2-5): (70-90). Exemplarily, the thickness ratio of the conductive polymer layer to the active material layer may be, but is not limited to, 2:70, 2:80, 2:90, 3:70, 3:80, 3:90, 4:70, 4:80, 4:90, 5:70, 5:80, 5:90. The conductive polymer layer is located between the active material layer and the current collector layer. The thickness of the conductive polymer layer affects the conductivity of the active material layer and the current collector layer. Within the above thickness ratio range, the conductive polymer layer can prevent thermal runaway from occurring and ensure the electron and ion transmission path between the current collector layer and the active material layer.
[0036] In some embodiments, in the conductive polymer layer, the mass percentage of the conductive polymer is 30% to 50%, and the mass percentage of polyethylene oxide is 5% to 20%. Exemplarily, the remaining components can be oxide solid electrolytes. Exemplarily, the mass percentage of the conductive polymer can be but not limited to 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48% or 50%. Exemplarily, the mass percentage of polyethylene oxide can be but not limited to 5%, 8%, 10%, 12%, 15%, 18% or 20%, etc. In this way, the conductive polymer layer is ensured to have good electronic conductivity and ionic conductivity at the same time, avoiding affecting the electronic transmission and ion transmission of the positive electrode active material. Polyethylene oxide can form a suitable number of hydrogen bonds with polyacrylonitrile within the above-mentioned mass content range.
[0037] In some embodiments, in the conductive polymer layer, the mass percentage of polyethylene oxide is 8% to 15%.
[0038] In some embodiments, in the active material layer, the mass percentage of polyacrylonitrile is 1% to 8%. For example, the mass percentage of polyacrylonitrile in the active material layer may be, but is not limited to, 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%. The content of polyacrylonitrile within the above range can achieve the purpose of flame retardancy, and will not affect the redox reaction of the positive electrode active material, and will not affect the battery capacity. Further, the mass percentage of polyacrylonitrile may be 1% to 4%.
[0039] In some embodiments, the active material layer further includes sericin. For example, sericin has certain adhesion and ion conductivity, which can further improve the adhesion between the active material layer and the conductive polymer layer and the ion conductivity of the composite electrode.
[0040] In some embodiments, the mass percentage of sericin in the active material layer is 1% to 2%. For example, the amount of sericin can be 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8% or 2%, etc. Within the above range, sericin can have a good connection effect and form a complete lithium ion transmission channel to improve ion conductivity, while avoiding excessive bonding that leads to reduced porosity and poor wettability of the electrolyte.
[0041] In some embodiments, in the active material layer, the mass percentage of the binder is 0.8% to 1.5%, the mass percentage of the conductive agent is 1.1% to 2%, and the rest is the positive electrode active material and unavoidable introduced substances, such as impurities, etc. Exemplarily, the mass percentage of the binder may be, but is not limited to, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, or 1.5%, etc. The mass percentage of the conductive agent may be, but is not limited to, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, or 2%, etc.
[0042] For example, the positive electrode active material may be lithium cobalt oxide LiCoO 2 , ternary materials NCM, NCA, lithium manganate LiMn 2 O 4 、LiFePO 4 Etc. For example, the positive electrode active material may also be a sodium-containing Prussian blue-type Na 2 MnFe(CN) 6 .nH 2 O, polyanionic compounds Na 3 V 2 (PO 4 ) 3 and NaFePO 4 And layered metal oxide material NaFeO 2 and Na 2 / 3 MnO 2 .
[0043] Exemplarily, the binder can be one or more of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride hexafluoropropylene (PVDF-HFP), polypropylene (PP), polyethylene (PE), styrene-butadiene rubber (SBR), nitrile rubber (NBR), polyacrylic acid, polyacrylonitrile, and sodium alginate.
[0044] Exemplarily, the conductive agent includes, but is not limited to, one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon nanotubes, carbon nanofibers, and graphene.
[0045] In some embodiments, the oxide solid electrolyte includes one or more combinations of NASICON-type solid electrolytes, perovskite-type solid electrolytes, LISICON-type solid electrolytes, and garnet-type solid electrolytes.
[0046] For example, the NASICON-type solid electrolyte may be, but is not limited to, Li 1+x Ti 2-x M x (PO 4 )3 , Li 1+x , Ge 2-x , M x (PO 4 ) 3 (0.1 < x < 0.7, M includes at least one of Al, Ga, In, and Sc). The perovskite-type solid electrolyte can be, but is not limited to, Li 3x , La (2 / 3)-x TiO 3 (0 < x < 0.16). The LISICON-type solid electrolyte can be, but is not limited to, Li 14 , ZnGe 4 O 16 . The garnet-type solid electrolyte can be, but is not limited to, Li 5 , La 3 , M 2 O 12 (M is Ta or Nb) or Li 7 , La 3 , Zr 2 O 12 .
[0047] Referring to Figure 2, a method for preparing a composite electrode includes the following steps S22 to S24.
[0048] S22, forming a conductive polymer layer and an active material layer on the current collector layer in sequence to obtain an intermediate.
[0049] Exemplarily, the conductive polymer layer can be coated on the current collector by intaglio, transfer, extrusion, or spraying; the active material layer can be coated on the conductive polymer layer by intaglio, transfer, extrusion, or spraying.
[0050] Exemplarily, the conductive polymer layer and the active material layer can be formed on both sides of the current collector layer in sequence.
[0051] S24, performing rolling treatment on the intermediate to obtain the composite electrode.
[0052] Exemplarily, since the conductive polymer layer close to the current collector layer contains a certain amount of conductive polymer, the overall coating softness of the conductive polymer layer is relatively large. After rolling, the active material layer far from the current collector layer is extruded into the conductive polymer layer, further reducing the interfacial impedance.
[0053] Exemplarily, when the conductive polymer layer and the active material layer are formed on both sides of the current collector layer, they are rolled together on both sides.
[0054] This application also provides a battery, which includes the composite electrode, the negative electrode, and the electrolyte of any one of the above embodiments, and the electrolyte contains tetraethylene glycol dimethyl ether solvent.
[0055] In the above-mentioned battery, the conductive polymer layer in the composite pole piece contains polyethylene oxide, and polyethylene oxide has an amorphous region. The amorphous region means that its molecular chain does not present an ordered crystal structure in the solid state, but is arranged in a disordered manner. By adding tetraethylene glycol dimethyl ether (TEGDME) to the electrolyte, tetraethylene glycol dimethyl ether is cross-linked with the amorphous region of polyethylene oxide to form a cross-linked phase, thereby reducing the crystalline phase of polyethylene oxide. The disordered structure of the cross-linked phase and the reduced crystalline phase help to provide higher ionic conductivity and improve the transmission effect of lithium ions. In other words, by reducing the crystallinity of polyethylene oxide, the polyethylene oxide chain segments are made more flexible in the electrochemical process. On the one hand, the ionic conductivity of polyethylene oxide can be improved, and on the other hand, more hydroxyl groups at the ends of the polyethylene oxide chains can form dynamic hydrogen bonds (CN-HO) with the cyano groups in polyacrylonitrile.
[0056] In some embodiments, the mass percentage of tetraethylene glycol dimethyl ether in the electrolyte is 4% to 10%. Exemplarily, the mass percentage of tetraethylene glycol dimethyl ether in the electrolyte can be, but is not limited to, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%, etc. Within the above range, polyethylene oxide can cross-link an appropriate amount of tetraethylene glycol dimethyl ether to improve ionic conductivity.
[0057] In some embodiments, the electrolyte includes bis(trifluoromethanesulfonyl)imide lithium salt, which accounts for 1% to 5% by mass of the electrolyte. For example, the mass percentage of trifluoromethanesulfonyl imide lithium salt in the electrolyte can be, but is not limited to, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc. Bis(trifluoromethanesulfonyl)imide lithium can also improve the ionic conductivity of polyethylene oxide.
[0058] Exemplarily, the electrolyte solvent includes one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl methyl carbonate, dimethyl carbonate, methylpropyl carbonate, ethyl propionate, propyl propionate, ethyl acetate, ethyl butyrate, propyl acetate, gamma-butyrolactone, fluoroethylene carbonate, fluoropropylene carbonate, 4-trifluoromethylethylene carbonate, methyl trifluoroethyl carbonate, and bistrifluoroethyl carbonate.
[0059] A method for preparing a battery includes the following steps S32 to S36.
[0060] S32, drying, rolling and die-cutting the composite electrode sheet and the negative electrode sheet;
[0061] S34, the composite electrode sheet and the negative electrode sheet obtained in step S32 are wound or stacked to form a battery cell;
[0062] S36, injecting electrolyte into the battery cell obtained in step S34, sealing, aging, and standing to obtain a battery.
[0063] The following are specific embodiments.
[0064] Example 1
[0065] Composite pole piece preparation:
[0066] (1) Preparation of conductive polymer layer slurry: Conductive polymer polyaniline, polyethylene oxide, oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 The mixture is mixed in a mass ratio of 4:1:5, added into deionized water and stirred evenly to obtain a conductive polymer layer slurry.
[0067] (2) Preparation of active material layer slurry: NCM811 positive electrode active material, polyacrylonitrile, sericin (purchased from Xi'an Ruiying Biotechnology Co., Ltd.), conductive agent carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 94.5:2:1:1.5:1, added to NMP solvent, and stirred evenly to obtain active material layer slurry.
[0068] (3) Aluminum foil is used as the current collector layer. The conductive polymer layer slurry is coated on the surface of the current collector layer by spraying and then dried at 80° C. (double-sided coating of the current collector is performed) to form a conductive polymer layer on the current collector layer.
[0069] The active material layer slurry is then applied to the surface of the conductive polymer layer coating by extrusion coating (double-sided coating), and then rolled after drying at 110° C. to form an active material layer on the conductive polymer layer.
[0070] After trimming and cutting, a lithium-ion battery composite electrode is obtained. Taking one side of the current collector layer as an example, the thickness of the conductive polymer layer close to the current collector layer is 3 μm, and the thickness of the active material layer formed on the conductive polymer layer is 80 μm.
[0071] Negative electrode sheet preparation
[0072] The negative electrode material (the negative electrode material includes graphite and silicon-carbon material, the mass ratio of graphite and silicon-carbon material is 95:5, wherein the silicon-carbon material: Lanxi Zhide New Energy Materials Co., Ltd., model S0332), the conductive agent superconducting carbon, the binder polyacrylic acid, and the binder dibutyl styrene rubber are prepared in a mass ratio of 94:1.5:3.0:1.5 to form a negative electrode slurry. The negative electrode slurry is coated on the current collector copper foil and dried and rolled at 105°C, and then the negative electrode slurry is coated and dried on the other side of the copper foil according to the above method, and then the prepared copper foil with a negative electrode active material layer on both sides is cold pressed to obtain a negative electrode sheet.
[0073] Battery preparation
[0074] Preparation of pre-electrolyte solution: LiPF 6 ) was added to the solvent (the solvent formula was a mixed solution of propylene carbonate: ethylene carbonate: dimethyl carbonate in a volume ratio of 1:1:1), and stirred thoroughly. 6 The concentration is 1 mol / L.
[0075] Tetraethylene glycol dimethyl ether and bis(trifluoromethanesulfonyl imide) lithium salt are added to the pre-electrolyte solution to obtain an electrolyte solution, wherein the mass percentage of tetraethylene glycol dimethyl ether in the electrolyte solution is 6%, and the mass percentage of bis(trifluoromethanesulfonyl imide) lithium salt in the electrolyte solution is 3%.
[0076] A polyethylene porous film with a thickness of 9 μm was selected as the separator, and the above-mentioned composite electrode sheet, separator and negative electrode sheet were wound into a battery cell with a capacity of about 10 Ah. The separator was located between adjacent positive and negative electrode sheets. The positive electrode was spot-welded with an aluminum tab, and the negative electrode was spot-welded with a nickel tab to obtain a battery cell.
[0077] The obtained battery cell is placed in an aluminum-plastic packaging bag, and after baking, the pre-electrolyte solution is injected, the bag is sealed, formed, and aged at 50° C. to obtain a battery.
[0078] Example 2
[0079] The preparation method of Example 2 is substantially the same as that of Example 1, except that:
[0080] Preparation of conductive polymer layer slurry: conductive polymer polypyrrole, polyethylene oxide, oxide solid electrolyte Li 0.33 La 0.57 TiO 3 The mixture was mixed in a mass ratio of 3:1.5:5.5, added into deionized water and stirred evenly to obtain a conductive polymer layer slurry.
[0081] Preparation of active material layer slurry: NCM811 positive electrode active material, polyacrylonitrile, sericin (purchased from Xi'an Ruiying Biotechnology Co., Ltd.), conductive agent carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 94.5:1:2:1.5:1, added to NMP solvent and stirred evenly to obtain active material layer slurry.
[0082] In the electrolyte, tetraethylene glycol dimethyl ether accounts for 4% by mass of the electrolyte, and bis(trifluoromethanesulfonyl)imide lithium salt accounts for 1% by mass of the electrolyte.
[0083] For the final composite tab, taking one side of the current collector layer as an example, the thickness of the conductive polymer layer close to the current collector layer is 2 μm, and the thickness of the active material layer formed on the conductive polymer layer is 90 μm.
[0084] Example 3
[0085] The preparation method of Example 3 is substantially the same as that of Example 1, except that:
[0086] Preparation of conductive polymer layer slurry: conductive polymer polythiophene, polyethylene oxide, oxide solid electrolyte Li 0.33 La 0.57 TiO 3 The mixture was mixed in a mass ratio of 5:0.8:4.2, added into deionized water and stirred evenly to obtain a conductive polymer layer slurry.
[0087] Preparation of active material layer slurry: NCM811 positive electrode active material, polyacrylonitrile, sericin (purchased from Xi'an Ruiying Biotechnology Co., Ltd.), conductive agent carbon black, and binder polyvinylidene fluoride were mixed in a mass ratio of 92.5:4:1:1.5:1, added to NMP solvent and stirred evenly to obtain active material layer slurry.
[0088] The mass percentage of tetraethylene glycol dimethyl ether in the electrolyte is 10%, and the mass percentage of bis(trifluoromethanesulfonyl)imide lithium salt in the electrolyte is 5%.
[0089] For the final composite tab, taking one side of the current collector layer as an example, the thickness of the conductive polymer layer close to the current collector layer is 5 μm, and the thickness of the active material layer formed on the conductive polymer layer is 70 μm.
[0090] Example 4
[0091] The preparation method of Example 4 is basically the same as the preparation method of Example 1, except that: Preparation of active material layer slurry: NCM811 positive electrode active material, polyacrylonitrile, sericin (purchased from Xi'an Ruiying Biotechnology Co., Ltd.), conductive agent carbon black, and binder polyvinylidene fluoride are mixed in a mass ratio of 95.5:2:0:1.5:1, added to NMP solvent and stirred evenly to obtain active material layer slurry.
[0092] Example 5
[0093] The preparation method of Example 5 is substantially the same as that of Example 1, except that tetraethylene glycol dimethyl ether is not added to the electrolyte.
[0094] Example 6
[0095] The preparation method of Example 6 is substantially the same as that of Example 1, except that the mass percentage of tetraethylene glycol dimethyl ether in the electrolyte is 2%.
[0096] Example 7
[0097] The preparation method of Example 7 is substantially the same as that of Example 1, except that the mass percentage of tetraethylene glycol dimethyl ether in the electrolyte is 13%.
[0098] Comparative Example 1
[0099] The preparation method of comparative example 1 is basically the same as that of example 1, except that: Preparation of conductive polymer layer slurry: conductive polymer polyaniline, oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 The mixture was mixed in a mass ratio of 5:5, added into deionized water and stirred evenly to obtain a conductive polymer layer slurry.
[0100] Comparative Example 2
[0101] The preparation method of Comparative Example 2 is basically the same as that of Example 1, except that: Preparation of active material layer slurry: NCM811 positive electrode active material, sericin (purchased from Xi'an Ruiying Biotechnology Co., Ltd.), conductive agent carbon black, and binder polyvinylidene fluoride are mixed in a mass ratio of 96.5:1:1.5:1, added to NMP solvent and stirred evenly to obtain active material layer slurry.
[0102] Comparative Example 3
[0103] The preparation method of comparative example 3 is basically the same as that of example 1, except that: Preparation of conductive polymer layer slurry: polyethylene oxide, oxide solid electrolyte Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 The mixture was mixed in a mass ratio of 5:5, added into deionized water and stirred evenly to obtain a conductive polymer layer slurry.
[0104] The composite pole pieces prepared in Examples 1 to 7 and Comparative Examples 1 to 3 or the batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were subjected to performance tests, and the test results are shown in Table 1 below.
[0105] Among them, the test conditions or test standards for each performance test item are:
[0106] First efficiency test: The batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were charged and discharged at a voltage range of 2.5-4.2V and 0.33C. The first cycle discharge capacity was compared with the upper charge capacity;
[0107] Diaphragm resistance test: Cut the rolled composite electrode into 4cm*4cm square pieces and place them under the poles of the test box for diaphragm resistance test.
[0108] Safety hot box test: The batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were tested. The test temperature started from 80 degrees Celsius and was increased at a rate of 5 degrees Celsius / min. The temperature was kept at 5 degrees Celsius for half an hour every half an hour until the battery started to smoke or catch fire and explode. The thermal runaway temperature was recorded.
[0109] Battery capacity: The batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were charged to 4.2 V at a constant current of 0.33 C, then charged to 0.05 C at a constant voltage, and then discharged to 2.5 V at 1 C to obtain the discharge capacity, which was then divided by the mass of the positive electrode active material in the composite electrode sheet of each embodiment;
[0110] Cycle performance test (cycle capacity retention rate): The batteries prepared in Examples 1 to 7 and Comparative Examples 1 to 3 were charged to 4.2 V at 0.5 C constant current, then charged to 0.05 C at constant voltage, and then discharged to 2.5 V at 0.5 C to obtain the capacity retention rate after 500 cycles.
[0111] Table 1
[0112]
[0113] As can be seen from Table 1 above, the comprehensive properties such as ionic conductivity of Examples 1 to 7 are improved relative to Comparative Examples 1 to 3, and have good flame retardant effects, indicating that the conductive polymer can ensure electronic conductivity while preventing thermal runaway. Polyacrylonitrile can further improve the flame retardant effect. In addition, a large number of dynamic hydrogen bonds are formed between the cyano group in polyacrylonitrile and the hydroxyl group at the end of the polyethylene oxide chain, strengthening the direct connection between the conductive polymer and the active material layer, reducing the interface resistance, and effectively improving the battery electrical performance while improving the battery safety.
[0114] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0115] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.
Claims
1. A composite pole piece, characterized in that: The composite pole piece includes a current collector layer, and at least one side of the current collector layer is sequentially formed with a conductive polymer layer and an active material layer in a direction away from the current collector layer, the conductive polymer layer includes a conductive polymer, polyethylene oxide and an oxide solid electrolyte, and the active material layer includes a positive electrode active material, a binder, a conductive agent and polyacrylonitrile.
2. The composite pole piece according to claim 1, characterized in that: The conductive polymer includes one or more combinations of polyaniline, polypyrrole and polythiophene.
3. The composite pole piece according to claim 1, characterized in that: The thickness ratio of the conductive polymer layer to the active material layer is (2-5): (70-90).
4. The composite pole piece according to claim 1, characterized in that: In the conductive polymer layer, the mass percentage of the conductive polymer is 30% to 50%; the mass percentage of the polyethylene oxide is 5% to 20%; Preferably, in the conductive polymer layer, the mass percentage of polyethylene oxide is 8% to 15%.
5. The composite pole piece according to claim 1, characterized in that: In the active material layer, the mass percentage of polyacrylonitrile is 1% to 8%; Preferably, in the active material layer, the mass percentage of polyacrylonitrile is 1% to 4%.
6. The composite pole piece according to claim 1, characterized in that: The active material layer also includes sericin.
7. The composite pole piece according to claim 6, characterized in that: The mass percentage of the sericin in the active material layer is 1% to 2%.
8. A battery, characterized in that: The battery comprises the composite electrode sheet according to any one of claims 1 to 7, a negative electrode sheet and an electrolyte, wherein the electrolyte contains a tetraethylene glycol dimethyl ether solvent.
9. The battery according to claim 8, characterized in that The mass percentage of tetraethylene glycol dimethyl ether in the electrolyte is 4%~10%.
10. The battery according to claim 8, characterized in that The electrolyte includes bis(trifluoromethanesulfonyl)imide lithium salt, which accounts for 1% to 5% by mass of the electrolyte.
